How Soundtracks Shape What We See: Analyzing the Influence of Music on Visual Scenes Through Self-Assessment, Eye Tracking, and Pupillometry - Ansani, Alessandro; Marini, Marco; D’Errico, Francesca; Poggi, Isabella (Frontiers in Psychology, 2020)
This article presents two studies that deepen the theme of how soundtracks shape our interpretation of audiovisuals. Embracing a multivariate perspective, Study 1 (N = 118) demonstrated, through an online between-subjects experiment, that two different music scores (melancholic vs. anxious) deeply affected the interpretations of an unknown movie scene in terms of empathy felt toward the main character, impressions of his personality, plot anticipations, and perception of the environment of the scene. With the melancholic music, participants felt empathy towards the character, viewing him as more agreeable and introverted, more oriented to memories than to decisions, while perceiving the environment as cozier. An almost opposite pattern emerged with the anxious music. In Study 2 (N = 92) we replicated the experiment in our lab but with the addition of eye-tracking and pupillometric measurements. Results of Study 1 were largely replicated; moreover, we proved that the anxious score, by increasing the participants’ vigilance and state of alert (wider pupil dilation), favored greater attention to minor details, as in the case of another character who was very hard to be noticed (more time spent on his figure). Results highlight the pervasive nature of the influence of music within the process of interpretation of visual scenes.